Perplexing purpura in two females: Rare case of autoerythrocyte sensitization syndrome - Ram R Tainwala; Meghna Phiske; Abhijith Raghuwanshi; Sukesh Mathapati; Ashwini K Manjare; Hemangi R Jerajani (Indian Dermatology Online Journal, 2013)
Autoerythrocyte sensitization syndrome is a psychologically induced painful bruising condition. Two female, 19 and 30-year-old presented with recurrent episodes of painful ecchymotic bruising over accessible areas of body. In the younger female, episodes were since 3 years and were precipitated by stress and trivial trauma. The elder female presented with similar lesions since 3 months which were spontaneous in presentation. There were no obvious psychiatric manifestations in either. Clinically, ecchymotic changes in various stages of development were seen. Routine hemogram and coagulation profile were normal. Histopathology showed extravasated erythrocytes, perivascular neutrophils and fibrinoid deposition. Intradermal injection of autologous whole blood produced a painful ecchymotic reaction after 2 h similar to the presenting lesions. Psychiatric evaluation revealed mild mixed depression - anxiety disorder in the younger female while the latter revealed no abnormalities. The diagnosis of autoerythrocyte sensitization syndrome was made based on clinical history and findings, positive autoerythrocyte sensitization test, psychiatric evaluation and absence of any other clinical or laboratory pathology.